(untitled) (Journal of the College of Basic Education, 2022)
The narratives of Imam Ibrahim bin Muhammad bin Al-Muntasher - may God have mercy on him - in Sunan Abi Dawood - an analytical study - it was found through the study of his life that he was one of the great followers of the followers as he was quoted from the followers who narrated on the authority of the Companions, may God be pleased with them , He is one of the scholars of Kufa and their asceticism, as he was a pious ascetic despite his frequent mention of God Almighty. He studied at the hands of the followers and their followers who transmitted hadiths from the Companions, may God be pleased with them. I extracted hadiths from their original sources, then studied the men of chain of transmission and then judged the chain of transmission of the hadith by looking at the The sayings of the scholars of wound and modification, Explaining after that the categories of isnad, and defining the strange words from the books of the strange hadith, then explaining the hadiths in the overall sense from the books of explanations, then I mentioned the benefits deduced from the hadith then the conclusion.